2000
DOI: 10.1161/01.atv.20.1.271
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Hemostatic Risk Factors for Ischemic Heart Disease

Abstract: Abstract-We have recently shown that fibrin D-dimer, tissue plasminogen activator (tPA) antigen, von Willebrand factor antigen, fibrinogen, plasma viscosity, and white cell count are associated with subsequent ischemic heart disease (IHD) in men aged 49 to 65 years in the Caerphilly Study from South Wales. We now report the contribution of major lifestyle factors to plasma levels of these new risk predictors for IHD. Results were available for up to 2188 men. The contribution of factors associated with lifesty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
100
1
7

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 42 publications
10
100
1
7
Order By: Relevance
“…Although some previous studies failed to demonstrate an association between homocysteinemia and fibrinogenemia (39,40), in the present work their correlation was significant (r=0.31, p=0.013), as it was in the studies by De Luis et al (16) (42), and the association between homocysteinemia and fibrinogenemia in our study concurs with previous findings indicating activity of the coagulation system in the setting of HHcy (43)(44)(45).…”
Section: Discussionsupporting
confidence: 91%
“…Although some previous studies failed to demonstrate an association between homocysteinemia and fibrinogenemia (39,40), in the present work their correlation was significant (r=0.31, p=0.013), as it was in the studies by De Luis et al (16) (42), and the association between homocysteinemia and fibrinogenemia in our study concurs with previous findings indicating activity of the coagulation system in the setting of HHcy (43)(44)(45).…”
Section: Discussionsupporting
confidence: 91%
“…In patients with arterial disease, two recent randomized placebo-controlled trials also showed no effect of high dose B-vitamin supplementation on hemostatic and inflammatory markers [13,14]. Similar to our findings, large cohort studies [15][16][17] have also shown at least a weak correlation between homocysteine and t-PA. Despite the positive correlation between baseline t-PA and homocysteine, we observed that vitamin supplementation paradoxically increased t-PA levels.…”
Section: A R O D R I G U E S V M M O R E L L I R C supporting
confidence: 90%
“…7 Sigaranın tromboembolik olaylara ve vasküler dolaşım bozukluğuna neden olduğu öteden beri bilinen bir gerçektir. 8,[25][26][27] Son yıllarda yapılan çalışmalarda plazma viskozitesinin diğer hemoreolojik faktörlerle de etkileşerek mikrosirkülasyonu dü-zenleyen çok önemli bir faktör olduğu ve trombotik olaylarda yükseldiği konusu üzerinde durulmaktadır. 28 Ayrıca sigaranın kan viskozitesi ve fibrinojen düzeyindeki yüksekliğe neden olabileceğine dair çalışmalar vardır.…”
Section: Discussionunclassified